The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3892/or.2018.6400
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a novel orally bioavailable CXCR4 inhibitor, AMD070, on the metastasis of oral cancer cells

Abstract: We have previously demonstrated that the stromal cell‑derived factor (SDF‑1)/CXCR4 system is involved in the metastasis of head and neck cancer. Additionally, it has been revealed that the blockade of CXCR4 by subcutaneous daily injection with AMD3100, a CXCR4 antagonist, may be effective in preventing metastasis in CXCR4‑related head and neck cancer. Recent investigations have suggested that AMD070, a novel orally bioavailable inhibitor of CXCR4, may be minimally invasive compared with AMD3100. In the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…In stark contrast, AMD3100 and niacin alone had no cytotoxic effects on the lymphoma cell lines. These findings are in line with already published data, where only the inhibition of migration of malignant and non-malignant cells for AMD3100 and growth inhibition for AMD070 have been reported [54,55]. However, our data indicate that the cytotoxic and/or apoptotic effects of AMD070 are increased by the addition of niacin and that these effects depend on the CXCR4 and CXCR7 expression patterns.…”
Section: Discussionsupporting
confidence: 93%
“…In stark contrast, AMD3100 and niacin alone had no cytotoxic effects on the lymphoma cell lines. These findings are in line with already published data, where only the inhibition of migration of malignant and non-malignant cells for AMD3100 and growth inhibition for AMD070 have been reported [54,55]. However, our data indicate that the cytotoxic and/or apoptotic effects of AMD070 are increased by the addition of niacin and that these effects depend on the CXCR4 and CXCR7 expression patterns.…”
Section: Discussionsupporting
confidence: 93%
“…In stark contrast, AMD3100 and niacin alone had no cytotoxic effects on lymphoma cell lines. These findings are in line with already published data, in which just inhibition of migration of malignant and non-malignant cells for AMD3100 and additionally growth inhibition for AMD070 were reported [42,43]. However, our data indicate that the cytotoxic and/ or apoptotic effects of AMD070 are increased by the addition of niacin and that these effects depend on the CXCR4 and CXCR7 expression patterns.…”
Section: Discussionsupporting
confidence: 93%
“…In preclinical studies, overexpression of CXCR4 has been demonstrated to dramatically increase lung and liver metastases of murine pancreatic cancer in tail vein metastasis assays in nude mice (106). Consistently, antagonizing CXCR4 inhibited lung metastasis of human tongue squamous cell carcinoma (107), esophageal cancer (108), breast cancer (109) in immunocompromized mice. Intra-arterially injected circulating CXCR4-expressing melanoma cells require SDF-1 signaling by mesenchymal stem cells that act as pericytes for extravasation to bone and liver and perivascular niche formation as demonstrated by humanized heterotopic bone formation assay (110).…”
Section: Sdf-1/cxcr4 Function In Tumor Biologymentioning
confidence: 80%